Ecomorphological comparison of Alouatta, Callicebus, and Cebus species inhabiting the Amazonian and Atlantic Forests - Villavicencio, José Eduardo Serrano (2022)
Morphological diversity is the result of a complex process that involves phylogenetic and ecological interactions, being the relative importance of each one of these factors dynamic and variable throughout the evolutionary process. Identifying patterns of morphological diversification and understanding its causes and effects are fundamental steps for studies of speciation, evolution and macroecology. In this scenario, I used three neotropical primate genera belonging to different evolutive radiations, Alouatta (Atelidae), Cebus (Cebidae), and Callicebus (Pitheciidae), as a model to explore the morphological evolution of this group of mammals. The main objective of this work was to reveal the patterns of morphological diversification present in these genera of primates widely distributed in the American continent, and to relate them through an integrated approach, with ecological and phylogenetic factors. For this purpose, I evaluated the material of these three genera held at the Museu de Zoologia da Universidade de São Paulo, São Paulo, Brazil. In total, I digitized 758 adult skulls of Alouatta (284), Callicebus (188), and Cebus (286) in dorsal, frontal, and lateral views. I obtained the phylogenetic information from online databases and by requesting directly to the authors of the most recent systematic reviews. I extracted 19 bioclimatic variables for each locality using the Raster package in R. I generated the morpho-geometric data by digitizing cranial landmarks in three different views, dorsal (12), frontal (12), and lateral (17). Finally, to calculate the correlation among climatic and geographical variables I performed a Two Separate Blocks Partial Least Square (PLS) Analysis on size and shape. My main results regarding size pointed out that: (1) Amazonian species of Alouatta and Cebus are bigger than their conspecifics from the Atlantic Forest, the opposite case of Callicebus; (2) there is a significant phylogenetic signal on cranial size of Callicebus; (3) Callicebus is the least sexually dimorphic genus among the three genera; (4) the allometric effect in Callicebus, percentage of size explaining shape, is negligible; (5) differently from Alouatta and Cebus, the PLS showed a significant correlation between size and climatic and geographical only in the case of Callicebus. In regards of shape, the most relevant results were: (1) allometry influenced significantly shape in Alouatta and Cebus, not in Callicebus; (2) Although the RV coefficient showed a lower total correlation between blocks of the PLS in Callicebus than in Alouatta and Cebus, its correlation is still iv significant. In view of these results, I can assure that, although being sintopic in most of their distributions, climatic and geographical have influenced directly but differently these three genera. In most cases, Alouatta and Cebus have responded similarly to the influence of abiotic variables what might suggest a similar process of diversification, taking advance of the processes of expansion and contraction of the Amazonia and the Atlantic Forest to colonize new ecoregions, contrastingly to Callicebus for which a series of vicariant events have been proposed as mainly path of diversification.